Tokyo 2020 event programme to see major boost for female participation, youth and urban appeal (2017)
The Executive Board (EB) of the International Olympic Committee (IOC) today approved the event programme for the Olympic Games Tokyo 2020. The decision marks a key milestone in the evolution of the Olympic programme by introducing youth and urban innovations, significantly improving gender equality, and reducing the overall number of athletes hence reducing the Games' footprint. Commenting on the decision, IOC President Thomas Bach said: "The fascinating new events that we approved today, together with the five new sports that were added to the Tokyo 2020 programme last year, represent a step-change in the Olympic programme. I am delighted that the Olympic Games in Tokyo will be more youthful, more urban and will include more women." The EB decision will lead to a net increase of 15 events, an overall reduction of 285 athletes from Rio 2016, and the highest representation of female athletes in Olympic history. In Tokyo, the number of mixed events will double from nine in Rio 2016 to 18. All new events will make use of existing venues.